2006
DOI: 10.1002/nme.1709
|View full text |Cite
|
Sign up to set email alerts
|

Non‐linear sloshing in partially liquid filled containers with baffles

Abstract: SUMMARYA finite element method is used for computing the non-linear sloshing response of liquid in a twodimensional rigid rectangular tank with rigid baffles. The potential formulation is considered for the liquid domain and a mixed Eulerian-Langrangian scheme is adopted. The solution is obtained by the Galerkin method. The fourth-order Runge-Kutta method is employed to advance the solution in the time domain. A regridding technique is applied to the free surface of the liquid, which effectively eliminates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(40 citation statements)
references
References 31 publications
8
31
0
Order By: Relevance
“…Nonlinear regime simulations showed that the hump topography was the most effective profile for reducing the nonlinear response of the fluid, as well as for reducing the overall amplitude of the free-surface elevations. This result is perhaps not a surprize, as previous studies have demonstrated the effectiveness of baffles (limit of an infinitely thin hump) in damping hydrodynamic effects in rectangular tanks (Biswal et al, 2006;Younes et al, 2007;Akyildiz, 2012;Xue et al, 2012). However, as far as the author is aware, this was the first systematic study of bottom topography in rectangular vessels leading to this conclusion.…”
Section: Conclusion and Discussionmentioning
confidence: 71%
“…Nonlinear regime simulations showed that the hump topography was the most effective profile for reducing the nonlinear response of the fluid, as well as for reducing the overall amplitude of the free-surface elevations. This result is perhaps not a surprize, as previous studies have demonstrated the effectiveness of baffles (limit of an infinitely thin hump) in damping hydrodynamic effects in rectangular tanks (Biswal et al, 2006;Younes et al, 2007;Akyildiz, 2012;Xue et al, 2012). However, as far as the author is aware, this was the first systematic study of bottom topography in rectangular vessels leading to this conclusion.…”
Section: Conclusion and Discussionmentioning
confidence: 71%
“…Cho and Lee [13,14], studied the sloshing liquid in a baffled tank by a nonlinear finite element method. Biswal et al [15] applied FEM on computing the non-linear sloshing response of liquid in a two-dimensional rectangular tank and circular cylindrical container with rigid baffles. The effect of baffle parameters including length, numbers and position on sloshing response were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of the TLD is discussed through prediction of coupling frequencies and response of the tank-structural system for different tank sizes, mass ratio between fluid and structure and tuning ratio. Bhattacharyya et al, 2006 had formulated a mixed Eulerian-Lagrangian finite element model to compute the non-linear sloshing amplitude of liquid in liquid filled rectangular and circular cylindrical containers subjected to sinusoidal base excitation. The solution is obtained by the Galerkin method.…”
Section: Introductionmentioning
confidence: 99%